Development of a functional point-of-need diagnostic for myeloperoxidase detection to identify neutrophilic bronchitis. Issue 23 (21st October 2016) - Wolfe, Michael G.; Zhang, Qiang; Hui, Christy; Radford, Katherine; Nair, Parameswaran; Brennan, John D.
Abstract : A paper-based analytical device was developed to rapidly detect myeloperoxidase in processed sputum for diagnosis of neutrophilic bronchitis. Abstract : With over 4.8 million Canadians suffering from chronic airway diseases, respiratory exacerbations are currently the leading cause of hospitalization in Canada. In cases of bacterial infection, neutrophil cell density increases from ∼10 million cells per gram to over 15 million cells per gram. As sputum is a direct discharge from the primarily affected areas of respiratory diseases, quantification of granulocytes (including neutrophils) can be used to effectively determine a course of patient treatment. Unfortunately this quantification is currently limited to labour-intensive and time-consuming cell counts. In the present study, we describe a simple one-step lateral flow test (LFT) that can semi-quantitatively determine myeloperoxidase (MPO), a biomarker found in neutrophils, in minimally-processed sputum samples. This point-of-need (PON) diagnostic device provides positive results observable to the naked eye after 15 minutes. 37 human sputum samples were quantified for MPO using the developed LFT and compared to neutrophil levels quantified through traditional cell counting. A trend between sputum MPO concentration and total neutrophils was observed, suggesting that the LFT has the potential to replace cell counting for neutrophil approximation to aid in directing therapies quickly at the point of need.